Digital Transformation of Labor Management in Vocational Agribusiness: An ADDIE-Based Evaluation of Efficiency and Accountability in Teaching Factory Units - Dyah Kusuma Wardani; Naning Retnowati; Paramita Andini; Mohammad Edwinsyah Yanuan Putra; Dhanang Eka Putra (Smart Society, 2026)
Background: The growing integration of digital technologies into agribusiness has reshaped organizational practices, yet labor management in many vocational Teaching Factory (TEFA) units continues to rely on paper-based procedures. Such practices frequently lead to attendance discrepancies, delays in payroll administration, and limited supervisory control. In response to these challenges, this study developed a digital labor-management system intended to strengthen operational efficiency and accountability in vocational agribusiness settings.. Methods: Adopting a research and development approach grounded in the ADDIE framework, the study combined system development with a stepped-wedge quasi-experimental evaluation. The research was conducted over twelve weeks in four TEFA units at Politeknik Negeri Jember and involved 25 casual workers and eight supervisors. The proposed platform integrated geolocation, geofencing, real-time productivity logging, and managerial dashboards. Data were analyzed using descriptive statistics and difference-in-differences models with fixed effects, while usability and technological readiness were assessed through the System Usability Scale (SUS) and Technology Readiness Level (TRL). Findings: The implementation of the system increased labor productivity by 13.4%, reduced cost-to-serve by 9.7%, shortened payroll-processing time by 41%, and lowered worker lateness by 48%. In addition, the accountability index improved by 0.88 standard deviations, indicating substantial gains in transparency and administrative performance. Conclusion: The findings suggest that digital labor management can enhance both efficiency and accountability, providing a practical foundation for the modernization of workforce administration in vocational agribusiness. Novelty/Originality of this article: This study offers an integrated framework that combines geolocation-based technology, the ADDIE model, quasi-experimental evaluation, and standardized usability and technology-readiness assessments within the context of vocational agribusiness labor management.